2020
DOI: 10.1097/mpg.0000000000002787
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cow's Milk Protein Allergy Prevalence With Socioeconomic Status in a Cohort of Chilean Infants

Abstract: Objectives: The aim of the study was to compare the cow's milk protein allergy (CMPA) prevalence in 2 cohorts of children from different socioeconomic strata. Methods: Prospective birth cohort that included patients from 2 hospitals providing care for a low- and high-income population, respectively. Healthy newborns ≥34 gestational weeks were recruited and followed up to 12 months by a monthly telephone survey. If ≥2 predefined symptoms/signs suggestive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
(32 reference statements)
1
10
1
Order By: Relevance
“…This clinical profile is similar to other South American regions, as reported by Errazuriz et al, highlighting a predominantly male population with familial atopy history and a similar diet distribution, albeit with a healthier status in their cohort 12 . Similar observations were made in a prospective study conducted in a private center in Chile 13 . However, in regions such as France, Kalach et al reported similar clinical patterns but with a lower proportion of exclusive breastfeeding at diagnosis (33%, less than that in our study) 14 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This clinical profile is similar to other South American regions, as reported by Errazuriz et al, highlighting a predominantly male population with familial atopy history and a similar diet distribution, albeit with a healthier status in their cohort 12 . Similar observations were made in a prospective study conducted in a private center in Chile 13 . However, in regions such as France, Kalach et al reported similar clinical patterns but with a lower proportion of exclusive breastfeeding at diagnosis (33%, less than that in our study) 14 .…”
Section: Discussionsupporting
confidence: 89%
“…12 Similar observations were made in a prospective study conducted in a private center in Chile. 13 However, in regions such as France, Kalach et al reported similar clinical patterns but with a lower proportion of exclusive breastfeeding at diagnosis (33%, less than that in our study). 14 Exclusive breastfeeding, slightly more prevalent in our CMPA patients' diagnosis (51.66% vs. 48.44%), has been shown to exert a protective effect against CMPA development compared with early infant formula use, as evidenced by a systematic review.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Mehaudy et al [71], conducting prevalence of cow's milk protein allergy among children in Argentina, has found a percent increase of 0.4% in 2004 to 1.2% in 2014 in the number of cases per year. Arancibia et al [87] found the overall prevalence of cow's milk protein allergy was 5.2%, with a 6 times higher prevalence in the high-income cohort (9.2%) compared with the low-income group (1.5%) in Chilean. Our study demonstrated that the prevalence of FA was 7.5% in Oceania, mainly conducted in Australia.…”
Section: Discussionmentioning
confidence: 99%